ADOLPH ZBO?IL - AN AUSTRIAN OFFICER IN THE TRANSVAAL ARTILLERY - Schmidl, Erwin A. (Scientia Militaria - South African Journal of Military Studies, 2012)
Whereas the German Major Richard Albrecht, the Commander of the Orange Free State Artillery, is a well-known figure of South African military history, this is not the case with Captain Adolph ZboÅ™il. ZboÅ™il (a Czech name, pronounced 'Sbor-shil') from 1886 to 1893 held the second-highest rank in the Transvaal Artillery. Admittedly, his achievements were less spectacular - and convincing - than Albrecht's and he left the Transvaal Artillery six years before the outbreak of the Second Anglo-Boer War. Still, it seems worthwhile to trace ZboÅ™il's career.